Morphological and molecular characterization of an Elaeis oleifera (H.B.K) Cortes germplasm collection located in Ucayali, Peru - Camacho Villalobos, Alina Alexandra; Serna Chumbes, Manuel Fernando; Flores Jaramillo, Jhoffre David; Flores, Hector; Manrique, Paulo; Bendezu, Jorge (Public Library of Science, 2021)
The African oil palm (Elaeis guineensis Jacq) is a crop that is widely distributed in tropical regions around the world; however, this crop is subject to limitations such as rapid trunk growth and susceptibility to bud rot and red ring diseases particularly in South America. To overcome these limitations, national breeding and conservation programs have been established, and there is a need to identify parental palms from natural populations of the American oil palm (E. oleifera H.B.K. Cortes) with desirable yield and morphological traits (i.e., yield production and bunch number) and with high genetic diversity. However, in Peru the morphological and genetic data related to this important crop is limited. In this study, we characterized the morphological and yield and estimated the genetic diversity using 12 neutral microsatellite markers (simple sequence repeats, SSRs) across 72 oil palm individuals belonging to the E. oleifera germplasm collection located in the tropical region of Ucayali, Peru. Our results showed that morphological and yield traits explained approximately 40.39% of the variability within the Peruvian germplasm. Furthermore, Yield Production was highly correlated with two yield traits: Bunch Number (0.67) and Average weight per bunch (0.78). Based on the yield and morphological traits, a clustering analysis was performed and three phenotypic groups were identified (1, 2 and 3) in which groups 1 and 3 showed high scores associated primarily with yield traits. Microsatellite markers revealed 143 alleles, 11.92 ± 4.72 alleles per locus (A) and an expected heterozygosity (He) of 0.69 ± 0.045. A structural analysis identified three populations (k = 3), that were not related to the phenotypic groups. Interestingly, a multiple allele background was identified within the groups using multilocus and phylogenetic relationship analyses. This is the first Peruvian report regarding E. oleifera that shows preliminary data of the morphological and yield traits and genetic data, and highlight the importance of this information to set up future steps to national breeding strategies and improve the conservation of genetic material of E. oleifera. Overall, these novel findings could contribute to the development of the local oil palm industry in Peru.